Development of an Android-Based Taekwondo Sports Coach Marketing Application - Lewi Abetnego Samosir; Rahma Dewi; Novita Novita; Indra Kasih (Randwick International of Education and Linguistics Science Journal, 2024)
The purpose of this research is to produce an application product in terms of the marketing field of android-based taekwondo martial arts trainers to make it easier for members (prospective athletes) to find competent trainers. This research is a type of research and development or Research and Development (R&D). The design used in this research is development research from Borg and Gall. The subjects of this study consisted of 25 people for small group trials and 40 people for large group trials. In the first small group (small) trial, the results of the research were obtained with a trial subject of 15 athletes and 10 coaches obtained a percentage of 92.86% with a decent category in the small trial. Based on the results of expert validation, it can be seen from the aspects of registration as a user 92%, registration as a coach 93.5%, ease of use 85%, and usefulness 93.5%. So on a small trial scale, application products in terms of the marketing field of android-based taekwondo martial arts sports trainers are valid. In the second group trial (large) obtained research results with 40 test subjects with 25 athletes with 15 coaches, a percentage of 94.00% was obtained with very feasible criteria. Based on the results of expert validation, the registration aspect as a user is 92.67%, the registration aspect as a coach is 94.33%, the aspect of usefulness is 94.67%, and the assessment on the aspect of ease of use of the coach is 93.67% (feasible). So on a large trial scale the application product in terms of the marketing field of android-based taekwondo martial arts coaches is valid. In this expert revision, there are no more revisions made by experts, so that the application product in terms of the marketing field of taekwondo martial arts sports trainers based on android is feasible.